Certification study guide : IBM Tivoli Configuration Manager (ITCM) version 4.2.2 - Gucer, Vasfi (IBM redbooks., 2005)
This IBM Redbooks publication is a study guide for IBM Tivoli Configuration Manager Version 4.2.2 and is aimed at the people who want to get IBM Certifications in this specific product. The IBM Tivoli Configuration Manager Certification, offered through the Professional Certification Program from IBM, is designed to validate the skills required of technical professionals who work in the implementation of the IBM Tivoli Configuration Manager Version 4.2.2 product. This book provides a combination of theory and practical experience needed for a general understanding of the subject matter. It also provides sample questions that will help in the evaluation of personal progress and provide familiarity with the types of questions that will be encountered in the exam. This publication does not replace practical experience, nor is it designed to be a stand-alone guide for any subject. Instead, it is an effective tool that, when combined with education activities and experience, can be a very useful preparation guide for the exam. Please note that the additional material referenced in the text is not available from IBM.